Assessing the relationship between organic farming practices and microbiological characteristics of organic lettuce varieties (Lactuca sativa L.) grown in Sao Paulo, Brazil - Maffei D.F. (2019)
Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica - CONCYTEC. Grant Number: 104-2016-FONDECYT